2017
DOI: 10.1111/jcpt.12549
|View full text |Cite
|
Sign up to set email alerts
|

Association ofNPR3polymorphism with risk of essential hypertension in a Chinese population

Abstract: This study suggested that NPR3 rs2270915 polymorphism was associated with decreased SBP level marginally in EH patients in a Chinese Han population, and the polymorphism may function through decreasing NPR3 mRNA expression and ANP level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…Another gene classified as dosage-sensitive is NPR3, deleted in one patient. A study in rats showed that this gene seems to be related to hypertension and blood pressure increase regardless of salt intake, but the effect in humans remains uncertain (Kuang, Zhou, Li, Tang, & Chen, 2017). Deletion of this gene did not show any physiological impact.…”
Section: Discussionmentioning
confidence: 99%
“…Another gene classified as dosage-sensitive is NPR3, deleted in one patient. A study in rats showed that this gene seems to be related to hypertension and blood pressure increase regardless of salt intake, but the effect in humans remains uncertain (Kuang, Zhou, Li, Tang, & Chen, 2017). Deletion of this gene did not show any physiological impact.…”
Section: Discussionmentioning
confidence: 99%
“…A promotor variant of NPR3 is linked to an increased risk of early-onset ischemic stroke. [22] In 2011, the Asian Genetic Epidemiology Network BP group identified genetic variants of NPR3 inducing blood pressure among East Asian population. Kato et al identified novel genome-wide associations between high blood pressure and NPR3 variants that affected SBP, DBP, stroke, and coronary artery disease.…”
Section: Raas Systemmentioning
confidence: 99%
“…O gene NPR3 está relacionado, em ratos, ao aumento de pressão sanguínea e hipertensão, independente do consumo de sal, mas o efeito de sua haploinsuficência em humanos permanece incerto (Kuang et al, 2017). Além desses genes, Nguyen et al (2015) destacaram outros genes como condicionalmente haploinsuficientes, ou seja, que apresentam algum fator de risco para a doença: SLC6A3, CDH18, CDH12, CDH10, CDH9, CDH6.…”
Section: Características Genômicas Da Região De 5punclassified